Physical performances and anthropometric characteristics of young elite North-African female soccer players compared with international standards - Hammami, M. A.; Klifa, W. B.; Ben Ayed, K.; Mekni, R.; Saeidi, A.; Jan, J.; Zouhal, H. (Science & Sports, 2020)
The reasons why North African women's football teams do not progress to the final phases of world cup competitions may be related to anthropometry and physical fitness. Therefore, the aim of this study was to compare anthropometric and physical fitness characteristics of young elite Tunisian female players with age-specific international standards. Twenty-four elite female players from the Tunisian national under 17 team (U17; 16.5 ± 0.4 y) participated in this study. Players were tested for anthropometry (body mass, body composition), football-specific cardiorespiratory endurance (Yo-Yo Intermittent Recovery Test Level 1; YYIRT1), power (countermovement jump, CMJ; squat-jump, SqJ; five-jump-test, 5JT), agility (t-test with and without ball), soccer skill (Loughborough Soccer Passing Test, LSPT) and speed (30 m sprint with 5 and 10 m splits). The results show that body mass and body fat percentage of Tunisian U17 elite female soccer players are higher than international standards and that endurance qualities and agility performances are similar to international data for the same age. However, in terms of strength and speed, performances of Tunisian female players are low or even very low compared with international standards. Consequently, physical training programmes of Tunisian female soccer should focus on increasing strength and speed fitness to be ready for international soccer competitions.